Development of Islamic Text-Based Reading Materials with a Genre-Based Approach - Linda Septiyana; Widhiya Ninsiana; Eka Yuniasih; Farida Nur Laily (Jurnal Pedagogy, 2022)
This study aims to develop Islamic text-based reading materials with a Genre-Based Approach as teaching materials for compulsory subjects for Islamic University students. The study used a Research and Development approach, where the data were collected through questionnaires and interviews. Qualitative data were analyzed using interactive analysis and quantitative data analysis used percentages. The research participants consisted of lecturers and 50 students from the Islamic Education Department. The data were collected through questionnaires and interviews. The result of this study indicated that designing Islamic text-based reading teaching materials with a genre-based approach is exceedingly needed. The content of the book consists of the following components: cover, preface, table of content, explanation text, recount text, descriptive text, narrative text, discussion text, hortatory text, news item text, references, and about the writer. Furthermore, the student's responses to the teaching materials designed were 0% disagreed, 13% less agreed, 52% agreed, and 35% strongly agreed. The average score is 3.22 and, if converted on a table with a scale of 4, includes it in a very good category. Therefore, an Islamic text-based reading material with a genre-based approach is worth applying by the students of the Islamic Education Department.